161k views
1 vote
Simplify: 9i(2+3i) enter your answer, in standard form, in the box ___

User Sydonie
by
5.0k points

2 Answers

3 votes
-54......................
User Opoe
by
5.5k points
2 votes

Answer:

Standard form is 9(2i-3) or (-27+18i)

Explanation:

To solve these type of question we should always keep in mind that i= √(-1)

and i² = (-1)

We have to solve the given form 9i(2+3i).

Now we start solving the question by simplifying the factors

9i(2+3i) = 18i+27i²

⇒ 18i +27(√-1)²

⇒18i +27(-1)

⇒18i-27

⇒9(2i-3)

So the simplified for is 9(2i-3) or (-27+18i)


User Kyw
by
4.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.